The Impact of Climate Conditions on Economic Production. Evidence from a Global Panel of Regions - Matthias Kalkuhl; Leonie Wenz (ZBW – Leibniz Information Centre for Economics, 2018)
We estimate the impacts of climate on economic growth using Gross Regional Product (GRP) for more than 1,500 regions in 77 countries. In temperate and tropical climates, annual temperature shocks reduce GRP whereas they increase GRP in cold climates. With respect to long-term climate conditions, one degree of temperature increase reduces output by 2-3%. The effect of annual or long-term precipitation is found to be less important and less robust among specifications. For projected global warming of 4°C until 2100, we find that regions lose 9% of economic output on average and more than 20% of output in tropical regions.
Keywords: E23; O11; Q54; Q56; 330; climate change; climate damages; climate impacts; growth regression